Sana’a and Women in Al-Maqalih’s Book of Sana’a Yemen - Jubran AL-Mamri, Muhammed (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
This paper aims to find out Sana'a's imageries in Al-Maqalih's book of Sana’a. It argues that Al-Maqalih has intensely and extensively used Sana’a as a metaphor. The analytical method has been used to analyze the Al-Maqalih's poems. Interviews with Al-Maqalih was carried out to clarify ambiguity in some of his poems. This study finds that Sana’a is metaphorically used by Al-Maqalih as poet’s beloved, as Ageless (Eternal Beautiful woman) and as a revolutionary and fighter woman, as Eve the wife of Adam (Ghaiman), the mother of poets and poetry, as a nymph, and an older woman.